2016
DOI: 10.1177/0363546515623032
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen-Year Survival of Endoscopic Anterior Cruciate Ligament Reconstruction in Patients Aged 18 Years and Younger

Abstract: 3Background. Within the young population, the literature examining the short term survival and the variables

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
138
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(155 citation statements)
references
References 40 publications
(59 reference statements)
10
138
3
Order By: Relevance
“…Perhaps this is not surprising since the average age of the patient group at follow-up was relatively young at 22 years. This is consistent with the findings of Morgan et al, 10 who also reported that 66% of their younger patient cohort were participating in strenuous or very strenuous sports at 15 years postsurgery. While not statistically significant, patients who rated their ability to perform as similar to before injury were more likely to still be playing their preinjury sport.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Perhaps this is not surprising since the average age of the patient group at follow-up was relatively young at 22 years. This is consistent with the findings of Morgan et al, 10 who also reported that 66% of their younger patient cohort were participating in strenuous or very strenuous sports at 15 years postsurgery. While not statistically significant, patients who rated their ability to perform as similar to before injury were more likely to still be playing their preinjury sport.…”
Section: Discussionsupporting
confidence: 92%
“…A more recent study by Morgan et al 10 showed that 69% of their young patient cohort (<18 years old at surgery) were able to return to preinjury level of sport. Overall, there are limited data available that specifically focus on return-to-sport rates in the younger ACL-reconstructed athlete, and the existing results are mixed.…”
mentioning
confidence: 98%
“…[2] Long-term follow-ups of 10 years or more have reported second injury rates between 23% and 27%. [35] Several factors have been implicated in second ACL injury risk, including graft placement,[68] graft type,[913] sex,[1416] age,[5, 14, 1719] time from surgery,[10, 20, 21] activity level,[22, 23] and aberrant neuromuscular and biomechanical adaptations. [24]…”
Section: Introductionmentioning
confidence: 99%
“…[19] Injury rates in this younger cohort have been reported almost as high as 30% in the literature. [5, 17, 20, 24] In addition, the increased risk in this group is apparent immediately upon returning to sports. The evidence strongly indicates that second ACL injury risk is greatest within the first 2 years after ACLR for young athletes returning back to high level sports.…”
Section: Introductionmentioning
confidence: 99%
“…In my experience the majority of revision ACL surgery occurs within the first 5 years. [22][23][24] In bioscrew fixation cases, the surgeon does not encounter healthy bone, rather a partially decomposed bioscrew in soft bone, which is definitely not an advantage in revision surgery.…”
mentioning
confidence: 99%